Increasing the Students’ Writing Narrative Text Ability Through Brainstorming Technique - Sari, Eny Maulita Purnama (Jurnal Pedagogy, 2017)
This script discusses the increasing students’ ability through brainstorming technique in teaching writing, especially in increasing students’ writing narrative text ability. This study is aimed at responding the following questions: (1) Can brainstorming as a technique increase the students’ Narrative paragraph writing Performance? (2) Can brainstorming as a technique improve the learning process?. The population of this research is the eighth grader of SMPN 3 BatanghariNuban. The number of population is 152 students. The researcher used sampling random technique to take sample. The research design was Classroom Action Research design. The instrument used to collect data was writing test because the students’ scores can be the basic data. The finding result shows that: (1) Brainstorming technique can make good students’ score in writing narrative text ability. (2) Brainstorming technique is effective in teaching writing, especially in writing narrative text.